Analisis Faktor Perilaku Dan Dukungan Suami Pada Ibu Hamil Kekurangan Energi Kronik (KEK) Dalam Menjalankan Program Pelayanan Kesehatan Di Wilayah Kerja UPTD Puskesmas Pancoran Mas Kota Depok Tahun 2022 - Ulya, Inayatul; Shaleha, Berliana Aullia; Putri, Sinta Amalia; Kuntoro, Toto; Luli, Marcianus Kai; Widyaningrum, Fransiska; Sari, Agustina (Universitas Tribhuwana Tunggadewi, 2023)
Chronic Energy Deficiency is a malnutrition problem during pregnancy caused by an unbalanced nutritional intake that resulted from a long-term energy deficiency. According to the Indonesian Primary Health Research data in 2018, only 25.2% of pregnant women received the supplementary feeding program, and the remaining 74.8% failed to receive the program. The data also states that the proportion of Indonesian pregnant women aged 15-49 years old were 17.3% high risk of Chronic Energy Deficiency. The study aimed to determine the community health degree based on the risk of events related to behavioral factors and husband support for pregnant women with Chronic Energy Deficiency, alternative problem solving, and problem-solving. The descriptive-analytic method was used with a qualitative approach through interviews with ten participants, stakeholders, and Chronic Energy Deficiency pregnant women. In addition, this study also uses the Ichikawa method to determine the problem cause. The results showed there was a lack of utilization of health service programs among pregnant women. To solve this problem, the alternative priority is to create educational content through the Instagram platform in terms of handling, monitoring, and preventing Chronic Energy Deficiency in pregnancy by taking into account the level of effectiveness and efficiency.